Pengaruh Pendapatan, Tingkat Pendidikan, Usia dan Jumlah Dompet Elektronik Terhadap Peluang Penggunaan QRIS para Pedagang UMKM - Della Berliana Putri Haryanto; Unggul Priyadi (ARBITRASE: Journal of Economics and Accounting, 2026)
The implementation of the Quick Response Code Indonesian Standard (QRIS) aims to expand financial inclusion and accelerate the digitalization of transactions within the MSME sector. However, in practice, the adoption of QRIS among MSME merchants remains uneven and has not yet reached its full potential. This study seeks to examine the likelihood of QRIS usage among MSME merchants and to identify the factors influencing its adoption. A quantitative approach was employed using a survey method targeting MSME merchants. The analysis utilized a Linear Probability Model (LPM), based on primary data collected through direct interviews consisting of structured questions related to QRIS and electronic wallets. The data were processed using SPSS version 29. The findings indicate that education level and income have a statistically significant effect on the probability of QRIS adoption. In contrast, age and the number of electronic wallets owned do not show a significant influence. These results suggest that the likelihood of QRIS usage is shaped not only by merchants’ economic capacity but also by their level of understanding and perceived need for digital payment systems. Therefore, more targeted socialization and educational strategies are necessary to enhance QRIS adoption among MSME merchants effectively.